Hubungan Aktivitas Fisik dengan Variabilitas Tekanan Darah pada Lansia di Daerah Istimewa Yogyakarta: The Relationship Between Physical Activity and Blood Pressure Variability Among Older Adults in the Special Region of Yogyakarta - Nessy Anggun Primasari; Erika Nurwidiyanti; Titis Eka Apriliyanti; Ika Nurfajriyani; Ari Teguh Santosa (LPPM STIKES Guna Bangsa Yogyakarta, 2026)
Background: Hypertension is a common non-communicable disease in the elderly and can lead to serious complications such as stroke, heart failure, and kidney disorders. The prevalence of hypertension in Indonesia continues to increase, including in the Special Region of Yogyakarta Province, which ranks fourth highest. According to a clinic in Yogyakarta, Anugrah Clinic, many elderly people diagnosed with hypertension rarely engage in physical activity, which can lead to high blood pressure. Regular physical activity can effectively lower blood pressure. Objective: To determine the correlation between physical activity and blood pressure variability in the elderly at the Anugrah Clinic in Kenteng Nogotirto subdistrict of Gamping, Sleman Regency D.I. Yogyakarta Province. Method: Quantitative correlational research with a cross-sectional approach. Sampling used a non-probability sampling technique, with a total sampling of 57 respondents. Global Physical Activity Questionnaire (GPAQ) questionnaire instrument, respondent characteristics questionnaire, sphygmomanometer. Statistical tests used Spearman rank. Results: There was a significant correlation between physical activity and blood pressure variability in the elderly. The statistical test results are p value 0.014 and r value 0.323. Conclusion: There was a significant relationship between physical activity and blood pressure variability among older adults at Anugrah Clinic, Kenteng, Nogotirto, Gamping, Sleman, Special Region of Yogyakarta, with a weak correlation strength. Healthcare professionals are encouraged to promote regular physical activity among older adults with hypertension as part of blood pressure management. These findings may serve as a basis for nurses to develop educational programs and interventions to increase physical activity among older adults.